Pelatihan Jurnalistik Dan Public Relations Bagi Siswa Syafana Islamic High School, Tangerang Selatan Oleh Program Studi Ilmu Komunikasi, Swiss German University - Deborah N. Simorangkir; Ezmieralda Melissa; Muninggar Sri Saraswati; A'an Suryana; Loina L.K. Perangin-Angin (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2019)
With the proliferation of social media and the rampant spread of hoaxes in the community, it is important that efforts are made to provide the next generation with media literacy and communication provisioning. Therefore, on April 23, 2019, the Communication and Public Relations Study Program, Swiss German University, held a workshop entitled "Spread Your Wings and Prepare Yourself to Compete in a Global World" at Syafana Islamic High School, BSD, South Tangerang. This activity was part of the Project Management and Leadership course. In addition to media literacy, this workshop also provided Syafana students with training on Public Relations, personality building, and the process of applying for jobs. In addition to presentations by lecturers and alumni, participants also practiced journalistic interviews as well as job interviews. This activity does not only have a positive impact on participants, but also for students who coordinated this program because while doing service activities to the community, students also develop skills such as: Leadership; Problem solving; Teamwork; Time management; and, communication – skills that are very useful in the real world.